Hijab as the Legal Identity and Spirituality of Muslim Women in Modern Social Dynamics - Danil, Muhammad; Effendi, Amri; Syarosy, Asa (LPPPM STAI Darul Hikmah Bangkalan, 2025)
This study explores the meaning, function, and social perception of hijab use in the lives of Indonesian Muslim women from the perspective of Islamic law, spirituality, and multicultural dimensions. The purpose of the research is to examine the normative basis of the obligation to wear the hijab in the Qur'an and Hadith, as well as to understand the subjective experiences of Muslim women of various ethnicities in Indonesia. This study uses a phenomenological qualitative approach with in-depth interview techniques with 20 Muslim women from Javanese, Sundanese, Madura, Batak, and Minangkabau ethnic backgrounds, followed by surveys as well as literature and documentation studies. The results of the study show that the hijab is not only understood as a sharia obligation, but also a symbol of spiritual identity, a means of self-protection, and a medium of identity negotiation in a pluralistic society. Muslim women interviewed acknowledged the challenges of social stigma, discrimination, and negative stereotypes, but they also affirmed the hijab as a source of spiritual strength and a symbol of ethno-religious pride. The practical implications of this study recommend the development of multicultural education programs in schools, teacher training on religious sensitivity, and media guidelines to portray the diversity of hijab practices in an equitable and inclusive manner